Indigenous peoples in Lima: the city as a maloca - Solís Fonseca, Gustavo (2013)
An account is made of the indigenous presence in the city of Lima, pointing out those who in some way assume their ethnic particularity in the context of the city. It is shown that Lima is an ethnically diverse city, as it is home to Aymara, Quechua, inhabitants of various Amazonian ethnic groups, and several groups of non-American descent that develop some level of community life that is evidenced in various ways. The data show the presence of Ashaninka (in Huaycán), Shipibo (in Cantagallo), Awajún people (in Ventanilla) and Matsiguenga (in Puente Piedra) who live more or less grouped together, to some extent as urban indigenous communities. It is noted that the city is a "melting pot" of the indigenous to generate non-indigenous, that is, Creole citizens or those assimilated to the greater western cultural society. How far is each one of them moving away from their indianity?